Predicting conservation priority areas in Borneo for the critically endangered helmeted hornbill (Rhinoplax vigil) - Hatten, Chloe Emma Ruth; Hadiprakarsa, Yokyok; Lee, Calvin Ka Fai; Jain, Anuj; Kaur, Ravinder *; Miller, Adam; Nyat Jun, Au; Khalid, Salwa; Dingle, Caroline (Elsevier, 2024)
The critically endangered helmeted hornbill (Rhinoplax vigil) is under threat around its Southeast Asian range due to hunting and habitat loss. Dependant on primary rainforest habitats, the species is thought to be highly sensitive to habitat disturbance. Compounding this is the threat of climate change where equatorial ecosystems, such as those found on Borneo, are predicted to increase in temperature and precipitation. It is therefore important to identify whether the species’ suitable habitats, both now and in the future, are protected from further anthropogenic disturbance. In this study we used species distribution models to assess the extent of suitable habitat for R. vigil across Borneo, an island which has undergone rapid deforestation in recent years, and a stronghold for the species. Using 302 R. vigil occurrence records, four environmental and three land-use cover variables, we modelled R. vigil current habitat suitability, and two future projections under climate change scenarios RCP 4.5 and RCP 8.5 for 2041–2060. Our results suggest that a quarter of Borneo's landmass is currently suitable for R. vigil. However, there is a steep decline in the predicted suitable habitat from 335,963 km2 (current scenario) to 73,170 km2 (future RCP 4.5), to 54,839 km2 (future RCP 8.5). Our model predicts that the amount of suitable habitat protected by current protected areas (PAs) and the planned Heart of Borneo (HoB) initiative will increase under future climate change, with the HoB protecting > 65 % of R. vigil suitable habitat across all projections. This is likely worsened by future land-use change not included in these models, which is a limitation to our study. We therefore encourage the connectivity of lowland PAs, and the continuation of HoB targets to prevent further decline of R. vigil habitat around Borneo. This study provides the first species-specific spatial assessment of the critically endangered helmeted hornbill distribution in response to climate change across current and planned protected regions in Borneo.